The Effect of Protein (as Fish Meal) on Rumen VFA Patterns of Molasses-fed Sheep - Abdullah, Hani (1984)
Experiments in vivo with molasses fed Merino sheep were carried out on a treatment reversal pattern examining the effects of fish meal (FM) supplementation on molasses intake and rumen volatile fatty acid (VFA) fermentation pattern. Differences in molasses intake due to protein supplementation were obsen'ed in the different periods. Regression analysis of VFA proportions against molasses intake during treatment periods indicated that the level of intake was a controlling factor in the patterns of VFA produced. Propionate and butyra'te were found to be positively, while acetate was negatively correlated with the molasses intake. The effects of intake and energyjproterin ratio on VFA pattern are also discussed.